(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
in the article on the basis of the territory of the sea and surrounding islands gat technologies geoecological zoned according to the level of the ecological situation in the aral sea and the region is zoned geoecological drawing a card and create his map information on the basis of the modern system geoaxborot aerospace GAT were used to investigate the complex ways from without, and to solve the issues of the aral sea problem and current situation in this area to improve the situation on the review of major projects i.e. xalqoro geoecological planting organizations.